2021
DOI: 10.5191/jiaee.2021.28390
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Educational Intervention Impacts on Food Security and Nutrition among Rural Farmers in El Salvador: A Mixed Methods Study

Abstract: Food insecurity in rural El Salvador has been a long-standing problem. This mixed-methods study explored rural farmers’ perceptions of their food security situation, identified critical food security needs, and examined farmers’ intentions to adopt measures to enhance their food security after an educational intervention to combat food insecurity in the area. For this community, the results reveal that access and utilization are the food security dimensions in which farmers perceive the most significant challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
1
0
1
Order By: Relevance
“…The results of this study indicated that, overall, Peruvian subsistence farmers are aware of the changes in the climate, especially changes in some of the feature expressions of climate variability, such as fluctuation in precipitation patterns, rising temperatures, and the incidence of extreme weather events. Several other studies in low-and middleincome countries in Latin America and other regions worldwide have comparable results on farmers' perceptions of trends in climate variability [78,79]. As confirmed by the results of this study, farmers' perceptions of CC included predominantly negative impacts on agricultural productivity and local natural resources.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results of this study indicated that, overall, Peruvian subsistence farmers are aware of the changes in the climate, especially changes in some of the feature expressions of climate variability, such as fluctuation in precipitation patterns, rising temperatures, and the incidence of extreme weather events. Several other studies in low-and middleincome countries in Latin America and other regions worldwide have comparable results on farmers' perceptions of trends in climate variability [78,79]. As confirmed by the results of this study, farmers' perceptions of CC included predominantly negative impacts on agricultural productivity and local natural resources.…”
Section: Discussionsupporting
confidence: 86%
“…Although others have shown that a prominent level of technical knowledge about climate variability is required to implement effective adaptation processes [76], the results of this study, like other research [77,78], indicated that general technical knowledge about CC is often low among subsistence farmers. The results of this study led to a similar conclusion where Peruvian farmers showed minimal technical understanding of the problem.…”
Section: Discussioncontrasting
confidence: 55%